Effect of Variation in Tapioca Adhesive Composition on Quality of Coconut Pulp Charcoal Bio-Broquette - Hrp, Abdul Maulub; Darvina, Yenni; Gusnedi, - (PILLAR OF PHYSICS, 2024)
Energy needs and consumption are still increasing, while energy sources continue to decrease due to their non-renewable nature. Renewable energy sources are needed as a substitute for alternative energy that is renewable, cheap, and environmentally friendly. Making bio-broquettes from coconut pulp charcoal is one of the studies that need to be studied and developed at this time. The abundance of coconut pulp waste is still not optimally utilized in managing its potential as a material for making bio-broquette. The composition of the adhesive used determines the quality of the bio-broquettes. This study aims to determine the effect of variations in the composition of tapioca adhesive on the calorific value, moisture content, density, ash content, fly content, carbon content, and burning rate of bio-broquettes. The material used for making bio-broquettes is coconut pulp charcoal. While the composition of tapioca adhesive that is varied is 30%, 40%, and 50%. The research used an experimental method, with 3 test treatments for each sample. The results obtained with 30%, 40%, and 50% tapioca adhesive for all test parameters have met the quality standards of charcoal bio-broquettes based on SNI 01-6235-2000. The best composition of tapioca adhesive is bio-broquettes that have a ratio of coconut pulp charcoal with 70% tapioca adhesive: 30% which produces the highest calorific value of 6,825.79 cal/gram, the lowest moisture content of 5.66%, density of 2.25 grams/cm3, the lowest ash content of 2.82%, the lowest fly substance content of 3.17%, the highest carbon content of 88.35%, and the highest burning rate of 0.1032 grams/minute